Mechanisms of Heavy Ion Reactions and De-excitation in Processes Initiated by Projectiles at Intermediate Energies, Using a Gamma Detector Array - Korir, Kipkirui Arap (My University, 2007)
The Doppler shift and the Doppler broadening of prompt gamma emissions were measured for some residues formed in the interaction of 33 A MeV 12C ions with a 63Cu target using the AFRODITE detector array at Faure, Cape Town. This is a potentially new technique to carry out nuclear interaction studies. Coincident gamma rays emitted by the residues are used in their identification. Detection at angles other than 90◦ with respect to the beam axis gives the magnitude of the mean Doppler shifts and the average linear momentum transfer. The Doppler broadening of the detected gamma lines at 90 ◦ with respect to the beam axis could give the residue recoil angular distribution. The precise shapes of the Doppler shifted and broadened gamma lines for each of the residues extracted, reveals the distribution, in magnitude and angle, of the momentum transferred in the interaction process. In addition, characteristic gamma energy transitions of each residue populated carry additional information on angular momentum (spin) transfer, production cross-section and nuclear excitation states. The measured residues show a unique distribution of momentum ranging from single nucleon transfer to complete damping of the projectile momentum. The measured observables are consistent with the existing data from other techniques, making the new technique viable option for studying nuclear interaction kinematics. A comparison of the experimental measurements with the predictions of the model developed in Milano 1 and GEANT4 calculations shows that the model developed in Milano model give a much better agreement compared to the GEANT4 calculations, attributed to the assumption of projectile break-up and re-emission process of some of the fragments during the first step of the nuclear interaction process.
Student Number : 0000713F - PhD thesis - School of Physics - Faculty of Science
Keywords: heavy ion reactions; intermediate energy; gamma detector array